Antimicrobial and antibiofilm activities of formylchromones against Vibrio parahaemolyticus and Vibrio harveyi - Sathiyamoorthi, Ezhaveni; Lee, Jin-Hyung; Tan, Yulong; Lee, Jintae (Frontiers in Cellular and Infection Microbiology, 2023)
ABSTRACT Gram-negative Vibrio species are major foodborne pathogens often associated with seafood intake that causes gastroenteritis. On food surfaces, biofilm formation by Vibrio species enhances the resistance of bacteria to disinfectants and antimicrobial agents. Hence, an efficient antibacterial and antibiofilm approach is urgently required. This study examined the antibacterial and antivirulence effects of chromones and their 26 derivatives against V. parahaemolyticus and V. harveyi. 6-Bromo-3-formylchromone (6B3FC) and 6-chloro-3-formylchromone (6C3FC) were active antibacterial and antibiofilm compounds. Both 6B3FC and 6C3FC exhibited minimum inhibitory concentrations (MICs) of 20 µg/mL for planktonic cell growth and dose-dependently inhibited biofilm formation. Additionally, they decreased swimming motility, protease activity, fimbrial agglutination, hydrophobicity, and indole production at 20 µg/mL which impaired the growth of the bacteria. Furthermore, the active compounds could completely inhibit the slimy substances and microbial cells on the surface of the squid and shrimp. The most active compound 6B3FC inhibited the gene expression associated in quorum sensing and biofilm formation (luxS, opaR), pathogenicity (tdh), and membrane integrity (vmrA) in V. parahaemolyticus. However, toxicity profiling using seed germination and Caenorhabditis elegans models suggests that 6C3FC may have moderate effect at 50 µg/mL while 6B3FC was toxic to the nematodes 20-100 µg/mL. These findings suggest chromone analogs, particularly two halogenated formylchromones (6B3FC and 6C3FC), were effective antimicrobial and antibiofilm agents against V. parahaemolyticus in the food and pharmaceutical sectors.